ERP System Based on Process Mining for Improving Logistic Management Efficiency in Small and Medium-Sized Enterprises in the Industrial Sector - Rojas, Kevin J. (2024)
The logistics process in small and medium-sized enterprises (SMEs) in the industrial sector is often exposed to various challenges, such as information loss, redundant activities, prolonged waiting times, and delivery failures, due to poor logistics management. In response to this problem, the implementation of an ERP system based on Process Mining is proposed to enhance the management of the logistics process in SMEs within the industrial sector. This system represents a comprehensive technological solution specifically designed to address logistics inefficiencies and optimize processes in the supply chain of these companies. As part of the evaluation methodology, performance indicators have been established to discuss the results obtained. These indicators have been defined using the Celonis tool, which has been employed for process mining. Findings obtained from the analysis of 30,000 records validate the optimization of the logistics process in companies within this sector, demonstrating a significant reduction in the percentage of key indicators for undesired activities in the logistics process.